UPAYA MENINGKATKAN KEMAMPUAN PRONOUNCIATION DENGAN MENGGUNAKAN LAGU PADA SISWA KELAS XI IPS 2 MAN 1 BANYUMAS SEMESTER GENAP TAHUN PELAJARAN 2018-2019 - Sri Mardiasih (Dwija Inspira: Jurnal Pendidikan Multi Perspektif, 2020)
In Indonesia, English has become a common language in everyday life in various sectors such as economy, politics, tourism and others. There are four basic skills in English that must be mastered, namely reading, listening, writing and speaking. And what is no less important in English is the pronunciation of the word or pronunciation, because if the pronunciation is not correct, the meaning will be different from the actual meaning. Mispronunciation of words in English often occurs, as experienced by students of Class XI IPS 2 MAN I Banyumas. This research was conducted on 23 students of class XI IPS 2 with 9 male students and 14 female students. The research data were collected through observation, tests and field notes. Technically, the method used in this research is through English songs. The students were asked to listen to and say a few words in the English song lyrics correctly. The average of all aspects in cycle 1 was 78.70 and cycle 2 was 87.88. Based on this, the use of songs as a learning medium can improve pronunciation skills in English.